Nazis of Copley Square : the forgotten story of the Christian Front - Gallagher, Charles R. (Harvard University Press, 2021)
"During WWII, a group of American Catholics openly embraced Nazism. Their armed wing, the Christian Front, stockpiled weapons for the revolution. Charles Gallagher unearths the history of these forgotten terrorists, the mainstream leaders who protected them, the powers who brought them down, and a society that has suppressed their memory"--
Keywords: Coughlin, Charles E : (Charles Edward), : 1891-1979; Christian Front; 1900-luku; 1900-talet; fasismi; natsit; roomalaiskatolinen kirkko; kristinusko; antisemitismi; antikommunismi; historia; Fascism and the Catholic Church : United States : History : 20th century; Nazis : United States : History : 20th century; Anti-communist movements : United States : History : 20th century; Christianity and antisemitism : United States : History : 20th century; Anti-communist movements; Christianity and antisemitism; Fascism and the Catholic Church; Nazis; Yhdysvallat; United States